When the Centre Cannot Hold : Patterns of Polarization in Nigeria - ClementI, F.; Dabalen, A.L.; Molini, V.; Schettino, F. (Wiley, 2018)
This paper advances the hypothesis that Nigeria is going through a process of economic polarization. The notion of polarization is concerned with the disappearance or non-consolidation of the middle class, which occurs when there is a tendency to concentrate in the tails, rather than the middle, of the income/consumption distribution. This paper uses newly available data and the relative distribution methodology (Handcock and Morris, 1998, 1999) to present new results on polarization. The findings confirm the sharp increase of polarization. Compared to 2003, the distribution of consumption has become more concentrated in upper and lower deciles in 2013, while the middle deciles have thinned. A between-group analysis shows the emergence of a macro-regional gap: while the South-South and South-West regions contribute mainly to polarization in the upper tail, households in the North East and North West zones—the conflict-stricken areas—are more likely to fall in the lower national deciles.